THE ANALYSIS OF FINANCIAL RATIOS AND EXTERNAL FACTORS AFFECTING EARNINGS PER SHARE OF SECURITIES IN THE MEDIA AND PUBLISHING SECTOR (MEDIA) LISTED ON THE STOCK EXCHANGE OF THAILAND (SET) - Lertjiraphat, Phatteera; Wimoonard, Thanapon (Journal of Graduate School Sakon Nakhon Rajabhat University, 2026)
This study explored the financial ratios and external factors affecting Earnings Per Share (EPS) of securities in the media and publishing (MEDIA) sector listed on the Stock Exchange of Thailand (SET). Annual reports of all 22 securities in the MEDIA sector were collected for the period 2020–2024 (B.E. 2563–2567), yielding a total of 110 data points over five years. Statistical methods employed for data analysis included descriptive statistics, correlation analysis, and multiple regression analysis. The analysis incorporates eight financial ratios: Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), Current Ratio (CR), Quick Ratio (QR), Debt to Equity Ratio (D/E), Interest Coverage Ratio (ICR), and Dividend Yield (DY). External factors considered were Gross Domestic Product (GDP), Minimum Loan Rate (MLR), and US Dollar to Thai Baht Exchange Rate (USD/THB). The findings revealed that the ICR and the MLR exhibited a statistically significant positive influence on EPS at the 0.01 level. GDP also showed a statistically significant positive influence on EPS at the 0.05 level. However, the US Dollar to Thai Baht Exchange Rate demonstrated a statistically significant negative influence on EPS at the 0.01 level. This research underscores the importance of interest coverage for managers aiming to drive EPS in the MEDIA sector and attract investment. Consequently, investors and relevant parties should also place significant emphasis on the ICR when making investment decisions.